Let A = ∫ 0 1 x x d x and B = ∫ 0 1 x − x d x .
Evaluate the value of ⌈ 1 0 0 0 0 ∣ A − B ∣ ⌉ .
Notations:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We don't need Stirling's approximation to prove convergence. Since ( 2 n ) ! is the product of the integers 1 , 2 , 3 , . . . , 2 n , all less than or equal to 2 n , it is clear that ( 2 n ) ! < ( 2 n ) 2 n . For that matter, convergence is shown even more simply by noting that ( 2 n ) 2 n ≥ 2 2 n , and comparing the series with a GP.
Log in to reply
Indeed, much easier!
Can I edit my solution to incoporate your proof of convergence?
Log in to reply
No worries. Of course, the fact that 0 ≤ n = 0 ∑ N n ! ( − 1 ) n ( ln x ) n x n ≤ x − x 0 ≤ x ≤ 1 , N ∈ N and the fact that x − x is continuous on [ 0 , 1 ] means that 0 ≤ n = 0 ∑ N ( n + 1 ) n + 1 1 ≤ ∫ 0 1 x − x d x for all N , which means that the series is convergent without further comment (and the Monotone Convergence Theorem makes the infinite sum equal to the integral),.
Problem Loading...
Note Loading...
Set Loading...
A = ∫ 0 1 x x d x
A = ∫ 0 1 e x ln ( x ) d x
A = ∫ 0 1 k = 0 ∑ ∞ k ! [ x ln ( x ) ] k d x
A = k = 0 ∑ ∞ ∫ 0 1 k ! [ x ln ( x ) ] k d x
Make u = − ln ( x ) , d u = − x 1 d x → d x = − e − u d u
A = k = 0 ∑ ∞ k ! ( − 1 ) k ∫ 0 ∞ e − u ( k + 1 ) u k d u
A = k = 0 ∑ ∞ k ! ⋅ ( k + 1 ) k ( − 1 ) k ∫ 0 ∞ e − u ( k + 1 ) [ u ( k + 1 ) ] k d u
Make t = u ( k + 1 ) , d t = d u ( k + 1 )
A = k = 0 ∑ ∞ k ! ⋅ ( k + 1 ) ⋅ ( k + 1 ) k ( − 1 ) k ∫ 0 ∞ e − t t k d t
A = k = 0 ∑ ∞ k ! ⋅ ( k + 1 ) k + 1 ( − 1 ) k Γ ( k + 1 )
A = k = 0 ∑ ∞ k ! ⋅ ( k + 1 ) k + 1 ( − 1 ) k k !
Make n = k + 1
A = n = 1 ∑ ∞ n n ( − 1 ) n + 1
Likewise:
B = ∫ 0 1 x − x d x
B = ∫ 0 1 e − x ln ( x ) d x
B = ∫ 0 1 k = 0 ∑ ∞ k ! [ − x ln ( x ) ] k d x
B = k = 0 ∑ ∞ ∫ 0 1 k ! [ − x ln ( x ) ] k d x
B = k = 0 ∑ ∞ ( − 1 ) k ∫ 0 1 k ! [ x ln ( x ) ] k d x
We already know this integral from A :
B = k = 0 ∑ ∞ ( − 1 ) k ( k + 1 ) k + 1 ( − 1 ) k
B = k = 0 ∑ ∞ ( k + 1 ) k + 1 1
Make n = k + 1
B = n = 1 ∑ ∞ n n 1
So, A − B will cancel out each term of odd n , remaining only the terms of even n :
∣ A − B ∣ = ∣ ∣ ∣ ∣ ∣ ∣ n = 1 ∑ ∞ ( 2 n ) 2 n − 2 ∣ ∣ ∣ ∣ ∣ ∣
∣ A − B ∣ = 2 n = 1 ∑ ∞ ( 2 n ) 2 n 1
This sum quickly converges to:
∣ A − B ∣ = 0 . 5 0 7 8 5 5 4 8 6
Correct to 9 decimal places. Thus:
⌈ 1 0 0 0 0 ∣ A − B ∣ ⌉ = 5 0 7 9
Proof of convergence of the series above:
( 2 n ) 2 n ≥ 2 2 n
( 2 n ) 2 n 1 ≤ 2 2 n 1
n = 1 ∑ ∞ ( 2 n ) 2 n 1 < n = 1 ∑ ∞ ( 4 1 ) n
n = 1 ∑ ∞ ( 2 n ) 2 n 1 < 3 1 q . e . d .